TAMILA SOROUSH'S EFFORT FOR A BETTER LIFE IN VEIL OF ROSES NOVEL BY LAURA FITZGERALD (2007) : AN INDIVIDUAL PSYCHOLOGICAL APPROACH - PRASETYANINGSIH, ESTI NUR (2014)
The major problem of this study is how effort Tami/a Soroush to get a better life and the objective of this study is individuality character based on reflected in real story of novel Veil of Roses is suitable with the theory by Alfred adler. The theory is individual psychological approach and major character in Veil of Roses novel. The type of this research is descriptive qualitative. Type of the data and the data source is taken from two data source: primary and secondary. The primary data source is Veil of Roses novel written by Laura Fitzgerald released in 2007. And secondary data sources is taken from books theor, other source and internet related to the study. The technique of collecting data is documentation. The steps are reading novel, classifj;ing and analyzing the data, taking note, and browsing to the internet. Based on the analysis, the researcher potrays some conclusion. The result, Individual Psychological Approach shows that Tami/a has all character in theory. This novel is about an Iranian girl who leaves her country and moves to America for her independence and better life.